The Emergence of the Digital Humanities. - Jones, Steven E. (Taylor & Francis Group, 2013)
What was once understood to be a transcendent virtual reality is now experienced as a ubiquitous grid of data that we move through and interact with every day, raising new questions about the social, locative, embodied, and object-oriented nature of our experience in the networked world.